2018
DOI: 10.1073/pnas.1802736115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular switch-like regulation enables global subunit coordination in a viral ring ATPase

Abstract: Subunits in multimeric ring-shaped motors must coordinate their activities to ensure correct and efficient performance of their mechanical tasks. Here, we study WT and arginine finger mutants of the pentameric bacteriophage φ29 DNA packaging motor. Our results reveal the molecular interactions necessary for the coordination of ADP-ATP exchange and ATP hydrolysis of the motor's biphasic mechanochemical cycle. We show that two distinct regulatory mechanisms determine this coordination. In the first mechanism, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 19 publications
6
48
2
Order By: Relevance
“…Also, both the N-and C-terminal domains appear to interact with incoming DNA (Figures 3, 4), again differing from results for T4 that suggest only the CTD interacts with DNA (51). Additionally, all five NTDs and CTDs appear to interact with DNA, in contrast to previous results we reported that only one subunit contacts the DNA (35). Further, the DNA structure differs considerably from canonical B-form DNA.…”
Section: Symmetry Breaking Prna-atpase Structurecontrasting
confidence: 84%
See 4 more Smart Citations
“…Also, both the N-and C-terminal domains appear to interact with incoming DNA (Figures 3, 4), again differing from results for T4 that suggest only the CTD interacts with DNA (51). Additionally, all five NTDs and CTDs appear to interact with DNA, in contrast to previous results we reported that only one subunit contacts the DNA (35). Further, the DNA structure differs considerably from canonical B-form DNA.…”
Section: Symmetry Breaking Prna-atpase Structurecontrasting
confidence: 84%
“…Based on sequence alignment with members of the FtsK branch of the ASCE superfamily, R146 was predicted to be the canonical ATPase 'arginine finger'. This prediction was supported by biochemical experiments designed to report trans-acting activity (31,35). While the current structural data could support R146 acting as the arginine finger, K105 seems equally well, if not better, positioned to assume this role.…”
Section: Figure 6 Domain Linker and Trans-acting Residues: (A) Sidevsupporting
confidence: 56%
See 3 more Smart Citations